Manipulating Charge Transfer and Transport via Intermediary Electron Acceptor Channels Enables 19.3% Efficiency Organic Photovoltaics. Issue 39 (21st August 2022) - Zhan, Lingling; Li, Shuixing; Li, Yaokai; Sun, Rui; Min, Jie; Chen, Yiyao; Fang, Jin; Ma, Chang‐Qi; Zhou, Guanqing; Zhu, Haiming; Zuo, Lijian; Qiu, Huayu; et al.
Abstract: Balancing and improving the open‐circuit voltage ( V oc ) and short‐circuit current density ( J sc ) synergistically has always been the critical point for organic photovoltaics (OPVs) to achieve high efficiencies. Here, this work adopts a ternary strategy to regulate the trade‐off between V oc and J sc by combining the symmetric‐asymmetric non‐fullerene acceptors that differ at terminals and alkyl side chains to build the ternary OPV (TOPV). It is noticed that the reduced energy disorder and the enhanced luminescence efficiency of TOPV enable a mitigated energy loss and a higher V oc . Meanwhile, the third component, which is distributed at the host donor–acceptor interface, acts as the charge transport channel. The prolonged exciton lifetime, the boosted charge mobility, and the depressed charge recombination promote the TOPV to obtain an improved J sc . Finally, with synergistically improved V oc and J sc, the TOPV delivers an optimal efficiency of 19.26% (certified as 19.12%), representing one of the highest values reported so far. Abstract : Intermediary electron acceptor channels are constructed for manipulating charge transfer and transport, via combing two non‐fullerene acceptors with less miscibility, which synergistically improves V oc and J sc, and enables ternary organic photovoltaic to exhibit a high efficiency of 19.3%.